Features of changes in the oral microbiome in pediatric patients with pronounced adenoid tissue hypertrophy and associated complications of the dentoalveolar system - Koshel , Orina; Deyeva, Julia (The Ukrainian Scientific Medical Youth Journal, 2026)
pronounced adenoid tissue hypertrophy (AAT) of II–III degree in children aged 3–9 years is one of the main causes of chronic mouth breathing, leading to dryness of the oral mucosa, changes in the pH environment, impaired colonization resistance, and the development of dysbiosis of the oral cavity and oropharynx microbiome. These changes are considered to be one of the possible mechanisms for the formation of anomalies of the dentoalveolar system (DAS), in particular open bite, class II malocclusion, and other craniofacial disorders, but their contribution and dynamics after removal of the obstruction remain insufficiently studied. The aim of the study was to evaluate the composition and diversity of the oral microbiome in children with severe stage II–III AAT associated with malocclusion compared to healthy children, as well as to track the dynamics of microbial changes 2 months after endoscopic adenotomy. Fifty children aged 3–9 years (mean age 5.8 ± 1.2 years) were examined: the main group consisted of 30 patients with clinically confirmed stage II–III AAT, chronic mouth breathing (>80% of the time and associated complications of the dentoalveolar system (DAS) (open bite or class II malocclusion according to cephalometry); the control group consisted of 20 healthy children without adenoid hypertrophy and complaints of breathing or bite problems. Material samples (smears from the oral cavity and oropharynx) were collected before surgery and 2 months after endoscopic adenotomy; 16S rRNA gene sequencing was performed, followed by analysis of alpha and beta diversity (Shannon, Simpson, Bray-Curtis, Jaccard, PERMANOVA indices), taxonomic composition at the genus level, LEfSe analysis (LDA > 3.0), and random forest for biomarker identification. Children with AAT showed a statistically significant decrease in alpha diversity (Shannon and Simpson, p < 0.05) and a clear separation of microbial profiles compared to the control group (PERMANOVA, p < 0,05), indicating pronounced dysbiosis. The main group was characterized by a significant enrichment of anaerobic genera: Prevotella (18.4 ± 4.2%), Fusobacterium (9.8 ± 2.9%), Parvimonas, as well as Lactobacillus and Bifidobacterium; particularly pronounced changes were observed in the subgroup with bite abnormalities (Prevotella 21.3 ± 4.1%, Fusobacterium 11.6 ± 3.2%, Parvimonas 4.9 ± 1.8%; p < 0,05). Haemophilus, Neisseria, and Veillonella dominated in the control group. After adenotomy, partial normalization of the microbial composition was noted: an increase in alpha diversity (p < 0,05), a decrease in the proportion of Prevotella and Fusobacterium, and an increase in Haemophilus, which correlated with clinical improvement (decreased mouth breathing, restoration of nasal breathing). LEfSe and random forest analysis identified a panel of dysbiosis biomarkers: Prevotella (AUC = 0.89), a combination of Fusobacterium + Parvimonas (AUC = 0.92). The data obtained confirm that pronounced adenoid hypertrophy in children is associated with anaerobic dysbiosis of the oral microbiome, which may play a role in the pathogenesis of DAS abnormalities against the background of prolonged mouth breathing. Endoscopic adenotomy contributes to the partial restoration of microbial balance and can be considered an important factor in the prevention and correction of DAS complications.